RESTAURANT TAX ENFORCEMENT AND REGIONAL INCOME OPTIMIZATION: A STUDY IN PEKANBARU CITY - Lubis, Baihaki; Haryono, Dodi; Artina, Dessy (Universitas Labuhanbatu, 2025)
The city of Pekanbaru, as the capital of Riau Province, continues to experience rapid development, supported by the improvement of facilities, including the growth in the number of restaurants, which contributes to the economy. Data from the Regional Revenue Agency (Badan Pendapatan Daerah) shows that revenue from restaurant taxes increased from 2021 to 2022, although it has not always reached the target, despite the fact that Pekanbaru serves as the center of all business activities, whether on a local, national, or international scale. This study uses an empirical juridical method, with clarification techniques that include interviews, questionnaires, and a literature review, aiming to identify the factors that hinder the enforcement of restaurant tax regulations in increasing Regional Original Revenue (Pendapatan Asli Daerah or PAD). The research findings indicate that law enforcement still requires a comprehensive approach through improvements in legal substance, structure, and culture. The obstacles faced include limited human resources, weak supervision, inefficient administrative systems, low taxpayer awareness, and inadequate sanctions. The success of law enforcement greatly depends on the synergy between the Regional Revenue Agency (Bapenda), the Civil Service Police Unit (Satpol PP), and the intensity of inspections to address restaurant tax violations.Keywords: Law Enforcement, Restaurant Tax, Local Original Income (PAD), Pekanbaru City